Exemptions for the benefit of commissions, judicial bodies and courts as one of the elements of shaping the scope of fiscal secrecy in France - Mariański, Michał (The Opole Studies in Administration and Law, 2025)
The aim of this article is to analyse and assess two of the eight groups of derogations distinguished in the French legal system within the framework of regulation of the scope of fiscal secrecy. The above will allow verifying the thesis concerning the extensive nature of the regulation of exceptions to the obligation to maintain fiscal secrecy in France. Another important issue will be the research question posed by the author about whether one of the characteristic features of French law, in particular administrative law, consisting in the introduction of general rules from which very extensive exemptions apply, is also applicable to tax law. The analysis of the method of regulating the issue of exemption from professional secrecy, referred to in tax law as fiscal secrecy, in the scope of derogations concerning committees and referring to judicial bodies and courts, is the main topic of the considerations in this study. The significance of the presented research for legal sciences is very important, as it will allow creating an introduction to broader analyses aimed at expanding the discussion in this aspect with additional comparative arguments. In order to meet the assumptions of this work, the author used both the historical-legal and dogmatic methods, as well as the comparative method as an auxiliary one. The results and conclusions from the conducted analyses refer to the issue of completeness of French regulations, their detailedness and compatibility with contemporary requirements of digital economic turnover. The conclusion also includes an analysis of the potential use of French solutions by the Polish legislator.